Surviving Sudden Environmental Change Answers From Archaeology - Cooper, Jago; Sheets, Payson (University Press of Colorado, 2012)
Archaeologists have long encountered evidence of natural disasters through excavation and stratigraphy. In Surviving Sudden Environmental Change, case studies examine how eight different past human communities-ranging from Arctic to equatorial regions, from tropical rainforests to desert interiors, and from deep prehistory to living memory-faced and coped with such dangers.